Determinación de la vulnerabilidad hídrica del río guano de la provincia de Chimborazo, en cantidad y calidad y su disponibilidad frente al cambio climático - Cabrera Alvarez, Lizbeth Jhoanna (2018)
The objective of this research was to determine the water vulnerability of the Guano River of the Chimborazo province, in quantity and quality and its availability to face the climate change. Initially, it was characterized the Guano River which crosses the canton of the same name from northwest to southeast with a length of 18.8 km, it is located within the sub-basin of the Chambo River which belongs to the Pastaza basin, on the High Andean climatic floor with altitudes from 2280 to 3800 meters above sea level, this area is identified by agricultural activities predominantly short-cycle crops, and cattle raising as there are large areas of pasture, in addition, they dedicate to industry and tourism. Then, the 10 sampling points were established from the Brook of Llio to Cubijies, in which the flow was measured, Giving as a result, that in the upper part it has a flow of 0.10 m3 / s and in the course of the river the amount of water increases due to the drains that it feeds, it flows into the Chambo River with a flow of 3.42 m3 / s, with the help of the Multiparameter, the dissolved oxygen and the place conductivity were measured, and water samples were taken, which were analyzed in the laboratory, it allowed to know the quality in which the water of the river is. According to the results of the laboratory, it determined that the Guano River has three quality indices; the high part is Acceptable, in the middle part is Medium Contaminated and in the bottom part is Contaminated, due to the activities carried out by the population of this sector. The data recorded by the meteorological station of the ESPOCH in the last 30 years allowed us to know the behavior of temperatures, rainfall, relative humidity and wind speed, which after the analysis show that it is closely related to each other, in some years it shows abrupt alterations that directly affect to the water system and through it to those who benefit from this resource. The Vulnerability of the micro-basin shows that it is in the MEDIUM category, which indicates that the Humidity Retention Index (IRH) is Very Low and the Water Use Index (WUA) values are Very Low, this shows that The existing Water Supply still covers the necessary Demands of the population, but the category already shows us the imminent risk that could occur over the years as it is threatened by climatic variation and the human action. This research may be useful for entities which seek the welfare of the canton.